Khīrī Wong : čhāk phrai nī nāi thưng thanākhān h̄æng khunkhao - Ph̨ōnphilai L̄œtwichā (Samnakphim Mūbān : Čhatčhamnāi dōi B̨ōrisat Khlet Thai, 1989)
On rural development in Khiri Wong Village, Amphoe Lan Saka, Nakhon Si Thammarat Province, southern Thailand.